Greening the Apocalypse A Pentecostal Eco-Eschatological Exploration - Williams, Andrew Ray (2018)
While Pentecostal theologians have lately begun examining the relationship between Pentecostal theology and ecology, little attention has been devoted to exploring the relationship between Pentecostal eschatology and ecotheology. In response, this study explores how wider Pentecostal eschatology can provide fresh opportunities for developing a Pentecostal eco-eschatology. In sum, I converge the eschatological contributions of Peter Althouse, Frank Macchia, and Larry McQueen on the point that the old earth is not annihilated at Christ's second coming, but is it is transformed into the new earth. I take ecotheological matters further by addressing the issues that emerge from a distinctly Pentecostal perspective - thoroughly pneumatological and praxis oriented. The result is an original, constructive eco-eschatological contribution to Pentecostal scholarship.
Keywords: Althouse, Peter; Earth (Planet); Religious aspects; Ecology; Religious aspects; Christianity; Eschatology; Christianity; History of doctrines; 1900; Kingdom of God; Macchia, Frank D, 1952-; McQueen, Larry R; New Creation; Theology, Pentecostal; Peer reviewed